Positive environmental modification of depressive phenotype and abnormal hypothalamic-pituitary-adrenal axis activity in female C57BL/6J mice during abstinence from chronic ethanol consumption - Pang, Terence Y.; Du, Xin; Catchlove, William A.; Renoir, Thibault; Lawrence, Andrew J.; Hannan, Anthony J. (Frontiers in Pharmacology, 2013)
Depression is a commonly reported co-morbidity during rehabilitation from alcohol use disorders and its presence is associated with an increased likelihood of relapse. Interventions which impede the development of depression could be of potential benefit if incorporated into treatment programs. We previously demonstrated an ameliorative effect of physical exercise on depressive behaviours in a mouse model of alcohol abstinence. Here, we show that environmental enrichment (cognitive and social stimulation) has a similar beneficial effect. The hypothalamic-pituitary-adrenal (HPA) axis is a key physiological system regulating stress responses and its dysregulation has been separably implicated in the pathophysiology of depression and addiction disorders. We performed a series of dexamethasone challenges and found that mice undergoing 2 weeks of alcohol abstinence had significantly greater corticosterone and ACTH levels following a DEX-CRH challenge compared to water controls. Environmental enrichment during alcohol abstinence corrected the abnormal DEX-CRH corticosterone response despite a further elevation of ACTH levels. Examination of gene expression revealed abstinence-associated alterations in glucocorticoid receptor (Gr), corticotrophin releasing hormone (Crh) and pro-opiomelanocortin (Pomc1) mRNA levels which were differentially modulated by environmental enrichment. Overall, our study demonstrates a benefit of environmental enrichment on alcohol abstinence-associated depressive behaviours and HPA axis dysregulation.